How to Measure a City's Metabolism. - Moore, S.K (IEEE spectrum)
Very little of what feeds and builds London comes from the city itself, and even less of the waste stays there. Instead, in order to feed, clothe, power, and build today's major metropolises you need the product of thousands of square kilometers outside the city limits. And you need thousands of square kilometers more to absorb the discards. So far, the largest urban area to have its footprint measured systematically is London. The results appeared in a report titled City Limits, released in 2002. It was found that London's ecological footprint was 49 million global hectares - 293 times its geographical area and equivalent to two United Kingdoms. On a per-person basis, Londoners took up 6.6 global hectares, putting them on a par with the Swiss and making them twice as frugal as the average American, but still more than three times as voracious as what the Earth can provide.